Exploring taxonomy and functional morphology in Campsurinae mayflies (Ephemeroptera: Polymitarcyidae) - Pantoja, Gabriel Martins (2024)
Ephemeroidea is a superfamily of Ephemeroptera that encompasses the only species ofmayflies in which nymphs are adapted to live in buried shelters. Polymitarcyidae is the most diverse family within this superfamily. Recently, the systematic classification of neotropical representatives of Polymitarcyidae has been revised in works based on conventional external morphological characteristics. Polymitarycidae exhibits some unique biological aspects in Ephemeroptera, such as adults having the shortest lifespan among mayflies and nymphs capable of silk production. Campsurinae is the most species-rich family of Polymitarcyidae, with a Pan-American distribution, showing greater diversity in the Neotropical region. Campsurinae nymphs construct U-shaped shelters in various aquatic substrates, and some species have been observed producing silk and manipulating silk fibers on shelter walls. In this study, as a consequence of our investigations on internal morphology, we describe the nymph of Tortopsis canum (Chapter I) and a new species of Campsurus (Chapter II). In the main study of this work, the objective was to analyze the histology and histochemistry of Malpighian tubules of Campsurinae species and species not belonging to Polymitarcyidae but still within Ephemeroidea. The studied Campsurinae species were Campsurus truncatus Ulmer, 1920, Campsurus sp., and Tortopsis canum Gonçalves, Da-Silva & Nessimian, 2011, which build shelters in different sediments (Chapter III). The studied species that do not belong to Polymitarcyidae were Campylocia burmeisteri (Hagen, 1888) (Ephemeroptera: Euthyplociidae) and Hexagenia albivitta (Walker, 1853) (Ephemeroptera: Ephemeridae) (Chapter III). Additionally, we analyzed the ultrastructure of the sperm of Campsurus violaceus Needham & Murphy, 1924 (IV). The Malpighian tubules of the studied Campsurinae species exhibit anatomy similar to the Malpighian tubules of C. burmeisteri and H. albivitta. However, the cell wall of the Malpighian tubules of the Campsurinae species contains secretory columnar cells, which are not found in the tubules of C. burmeisteri and H. albivitta. The secretory columnar cells of the Campsurinae species display cytoplasm containing granules that react positively to Periodic Acid-Schiff (PAS) and Bromophenol Blue tests, confirming the secretion of glycoprotein material by the Malpighian tubules. The morphology found in the sperm of C. violaceus shows variations that may serve as important phylogenetic signals in evolutionary studies of mayflies, such as the pattern of protofilaments in the accessory tubules, the arrangement of accessory bodies, and the number of mitochondria. Keywords: ephemeroidea, south america, mayflies, silk production, sperm, ultrastructure.